Genetic Variability of Echinochloa crus-galli Ecotypes from West Java, Indonesia, by RAPD Analysis - Pasaribu, Pesta Maria Hotnauli; Rizqullah, Ramadaniarto; Ardie, Sintho Wahyuning; Guntoro, Dwi (Department of Agronomy and Horticulture, IPB University, 2025)
Echinochloa crus-galli (Barnyardgrass: Poaceae), is one of the most detrimental weeds in rice fields globally. As one of the leading rice producers in Indonesia, controlling barnyard grass in rice fields in West Java province is of great importance. Information on the genetic variability of barnyard grass is necessary to determine proper weed control. A molecular marker is considered the most accurate tool in determining genetic variability as its profile is unaffected by the environment. The objective of this study was to evaluate the genetic variability of barnyard grass collected from seven sub-districts in West Java province, Indonesia, using RAPD markers. Genomic DNA of barnyard grass ecotypes from “Bayusari”, “Majalaya”, “Klari”, “Cugenang”, “Cianjur”, “Ciomas”, and “Ciampea” sub-districts were analyzed using eight RAPD primers and resulted in a total of 87 reproducible amplicons. Of these amplicons, 59 were polymorphic, and 28 were monomorphic, with a polymorphism percentage ranging from 37.5-92.8%. Polymorphism information content (PIC) values ranged from 0.21 to 0.41, indicating the used RAPD markers are highly informative. All seven ecotypes were divided into three distinct groups with a coefficient level of 0.77 in a dendrogram constructed following the UPGMA clustering method. Group 1 consisted only of the “Bayusari” ecotype. Group 2 consisted of “Majalaya”, “Klari”, and “Cugenang” ecotypes, while Group 3 consisted of “Cianjur”, “Ciomas”, and “Ciampea” ecotypes. This research indicated remote dispersal of E. crus-galli, since ecotypes from distant locations were found to be closely related